Aneka Ragam Identitas Islam Dari Berbagai Perspektif - Andri Qurniawan; Ahmad Nurhuda; Hamid Abdillah; Restu Dwi Cahya (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
Variety is a variety of things, while identity is a sign of self-identification. With identity, we will be more easily recognized by others. Then when related to the word "Islam" is an identity of a variety of Islam that prioritizes substance. Islam itself has the meaning of peace, every Muslim is obliged to spread peace as a form and religious identity. Islam is not enough just to take the shahada, but a Muslim is obliged to uphold the value and essence of the shahada, uphold the teachings that are Rahmatan lil 'alamin as Allah Almighty sent the prophet Muhammad (peace be upon him) not except as mercy.